The potential contribution of microplastic pollution by organic fertilizers in agricultural soils of Bangladesh: quantification, characterization, and risk appraisals - Rana, Md. Mishail; Haque, Md. Rashedul; Tasnim, Sikder Sanchita; Rahman, Md. Mostafizur (Frontiers in Environmental Science, 2023)
Although plastics are being recycled worldwide, a significant amount of plastic is still directly exposed to the environment and, in the end, forms microplastic (MP) particles (<5 mm). Soil is a significant sink for plastic waste. Thus, MP is considered an emerging threat to terrestrial ecosystems. Among several sources, organic fertilizer can be a potential source of MP to contaminate agricultural soils. Therefore, it is hypothesized that commercial organic fertilizer acts as a carrier of MP to agricultural soils in Bangladesh. Hence, 18 organic fertilizers were collected from different local markets in Bangladesh and subjected to the following available MP separation/extraction techniques. Then, a series of experimental steps were conducted, such as microscopic inspection, identification through Fourier-transform infrared spectroscopy (FTIR), scanning electron microscope (SEM), and energy-dispersive X-ray analysis (EDAX), to identify and characterize MP. The data were analyzed statistically using both qualitative and quantitative approaches. On average, 1,529.62 ± 420.2 MP items/kg of organic fertilizer were detected in the study, ranging from 433.33 ± 152.75 items/kg to 3,466.67 ± 1,357.69 items/kg in different organic fertilizers. The size range of 0.5 mm–1.00 mm (30%) was predominant among five different size ranges. The fiber was dominant over various shapes, and seven colors were observed, with black being the most prevalent. Overall, in a year, 971.31–1,387.37 items/m3 area was introduced through organic fertilizer to land. These MPs further contaminate soil biota and groundwater by their distribution pattern. According to the polymer hazard index (PHI), pollution load index (PLI), and potential ecological risk index (PERI), this organic fertilizer belongs to hazard categories III, V, and extreme danger, respectively. This study clearly explains the presence of MP in commercially available organic fertilizers and their probable effects. This could be applicable in further policy planning to reduce contaminants in formulating organic fertilizers.